2016
DOI: 10.4238/gmr15047178
|View full text |Cite
|
Sign up to set email alerts
|

HPV genotype analysis for women in Shaanxi Province of China

Abstract: ABSTRACT. The aim of this study was to examine the subtype distribution of human papilloma virus (HPV) in women in the Shaanxi Province of China. A DNA chip, along with polymerase chain reaction amplification and reverse dot blot technology, was adopted to analyze the HPV genotypes of 22,937 cases of cervical cell specimens. The HPV infection rate was 18.70%, wherein high-risk, low-risk, and high-and low-risk multiple infection rates were 15.75, 2.96 and 1.91%, respectively. High-risk infections accounted for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
(10 reference statements)
0
3
1
Order By: Relevance
“…HPV subtypes examined in our study, HPV58, 52, and 16 had the highest prevalence in overall, single-type and multiple-type infected participants, which is slightly different from some data for screening [17]. The study also showed that the most common infection was with HPV58, which was detected in 10.34% of the women with vaginitis.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…HPV subtypes examined in our study, HPV58, 52, and 16 had the highest prevalence in overall, single-type and multiple-type infected participants, which is slightly different from some data for screening [17]. The study also showed that the most common infection was with HPV58, which was detected in 10.34% of the women with vaginitis.…”
Section: Discussioncontrasting
confidence: 95%
“…To further investigate the relationship between vaginitis and HPV infection, 447 patients with vaginitis were chosen for HPV genotyping results, showing that the total HPV infection rate was 39.60% in women with vaginitis. Previous studies have focused on the prevalence of HPV infection in different countries [16,17] and within China, and the prevalence varies from 9.9 to 31.9% in different areas in China [18][19][20].In our study, the infection rate was 39.60%, indicating a higher frequency in women with vaginitis. Considering this high prevalence, it is indispensable to know the HPV genotype distribution for vaccine development in women with vaginitis.…”
Section: Discussionmentioning
confidence: 45%
“…In our study, the overall HPV prevalence rate was 17.83% (937/5,255) in Shenzhen city. However, HPV infection rates are known to vary across different regions in China (7.3% in Guangdong, 15 9.9% in Beijing, 16 10.3% in Liaoning, 17 18.7% in Shaanxi, 18 and 24.7% in Xinjiang 19 ), and across different countries (8.0% to 27.3%). 9,[20][21][22] Demographic factors such as ethnicity, socioeconomic status, health conditions, and education level may contribute to the uneven distribution of HPV incidence.…”
Section: Discussionmentioning
confidence: 99%
“…The 21 HPV GenoArray Diagnostic Kit is a qualitative polymerase chain reaction (PCR)-based test used for the detection and determination of 21 specific HPV DNAs in cervical specimens. The 21 HPV genotypes are divided into 15 high-risk genotypes (HPV 16,18,31,33,35,39,45,51,52,53,56,58,59, 66 and 68) and 6 low-risk genotypes (HPV 6,11,42,43,44,CP8304), and the specific detection steps were followed in strict adherence to instructions, as described previously. 13,14 Briefly, the HPV DNA extracted from cervical samples was amplified using PCR, and then hybridized with specific HPV probes located inside the membrane strip, followed by the use of the enzyme immunoassay method to obtain colorimetric results.…”
Section: Hpv Genotype Testingmentioning
confidence: 99%